La fritura de los alimentos : pérdida y ganancia de nutrientes en los alimentos fritos (2008)
ABSTRACT: Deep-fry is one of the simples food cooking process that is used mainly to prepare potatoes. This cook method consist to heat comestible oil at 160 to 180°C, at this temperature food fried like potatoes gets “crust” and develop a good taste. During the fry process food composition may change according to the type of food as well as the frying method applied. Food modification occur mostly in total cholesterol, fat content and also fatty acids composition, even though, most of the vitamins are retained in fried food, some unlike changes occur in high carbohydrates food content such as cholesterol oxidation and acryl amides formation that are related to cardiovascular diseases.